Chemical Investigation of Major Constituents in Aloe vera Leaves and Several Commercial Aloe Juice Powders. (23rd November 2019) - Zhang, Yuehong; Bao, Zhichao; Ye, Xiaoyan; Xie, Zhaoyang; He, Kan; Mergens, Bill; Li, Wenjie; Yatcilla, Mike; Zheng, Qunyi
Abstract: Background: There are a substantial number of papers in the scientific literature reporting on the chemical composition of the Aloe vera plant. None of these investigations are truly comprehensive nor address the differences in composition that occur through processing variations in fresh leaves and commercially available product forms. Objectives: This work was to analytically examine a range of these forms and compile the findings. Methods: Fresh A. vera leaves and a number of commercial aloe juice powders were investigated for their major chemical constituents. Samples included fresh leaves from China and Mexico, plus commercial powders from different manufacturers made from different plant parts and/or manufacturing processes. The test results include moisture, ash, fiber, protein, lipids, minerals, organic acids, free sugars, and polysaccharides. The analytical methods employed comprise inductively coupled plasma-optical emission spectroscopy for minerals, high-performance anion-exchange chromatography equipped with pulsed amperometric detection for free sugars, HPLC for organic acids, and size exclusion chromatography (SEC)–multi-angle laser light scattering (MALS)–differential refractive index (dRI) for polysaccharide analyses. The absolute MW and MW distribution were determined using MALS measurement. Results: The major constituents of A. vera fresh leaf are fibers, proteins, organic acids, minerals, monosaccharides, and polysaccharides, which accounted for 85–95% of the total composition determined. In the commercial powdered aloe juice samples, four major components—organic acids, minerals, monosaccharides, and polysaccharides—accounted for 78–84% of the total composition. Apart from the four major components, products manufactured by ethanol precipitation contained high amounts of fiber and protein, while the free sugars were removed. In ethanol-precipitated products, the polysaccharide MW was less affected by manufacturing conditions and the concentration of aloe polysaccharides was higher than in products made in the nonethanol manufacturing processes. The overall chemical profiles were found to be consistent, except for the MW and content of polysaccharides in the commercial aloe samples analyzed, which were largely dependent on the types of manufacturing processes employed. Conclusions: This present study provides a comprehensive investigation of the major chemical composition of A. vera leaf and commercially derived products. The use of the SEC combined with MALS and differential RI detectors has proved to be an improved tool for the accurate determination of polysaccharide MW and contents of the various commercially available A. vera products in this study.